Construction of Reverse Super Edge Magic Total Graphs - Masthan Raju, U.; Sharief Basha, S. (International Journal of Engineering and Technology, 2018)
In this paper, we investigate the adjacency matrix ofÂ reverse super edge magic vertex graph and use this graph to construct other reverse super edge magic graphs with the same edge weight set. Additionally, by combining known reverse super edge magicÂ labelled graphs, we give a construction for a new reverse super edge magic graphÂ Â